2017
DOI: 10.1088/1751-8121/aa920d
|View full text |Cite
|
Sign up to set email alerts
|

On divergences in non-minimal ${ \newcommand{\N}{{{\mathcal N}}} \N=4}$ conformal supergravity

Abstract: We review the question of quantum consistency of N = 4 conformal supergravity in 4 dimensions. The UV divergences and anomalies of the standard ("minimal") conformal supergravity where the complex scalar ϕ is not coupled to the Weyl graviton kinetic term can be cancelled by coupling this theory to N = 4 super Yang-Mills with gauge group of dimension 4. The same turns out to be true also for the "non-minimal" N = 4 conformal supergravity with the action (recently constructed in arXiv:1609.09083) depending on an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 42 publications
(142 reference statements)
0
12
0
Order By: Relevance
“…It is true that these theories are power-counting renormalizable but the one-loop beta-functions turns out to be non-vanishing [37] and therefore they suffer from a conformal anomaly. The latter leads to serious problems in Weyl gravity as the conformal symmetry is gauged and therefore leads to inconsistencies [38][39][40]. Let us also note that one may arrive at the same conclusion by the calculation of the chiral gauge anomalies of the SU(4) R-symmetry [41] and by recalling that all anomalies are arranged in the same multiplet of the N = 4 superconformal symmetry.…”
Section: Discussionmentioning
confidence: 81%
“…It is true that these theories are power-counting renormalizable but the one-loop beta-functions turns out to be non-vanishing [37] and therefore they suffer from a conformal anomaly. The latter leads to serious problems in Weyl gravity as the conformal symmetry is gauged and therefore leads to inconsistencies [38][39][40]. Let us also note that one may arrive at the same conclusion by the calculation of the chiral gauge anomalies of the SU(4) R-symmetry [41] and by recalling that all anomalies are arranged in the same multiplet of the N = 4 superconformal symmetry.…”
Section: Discussionmentioning
confidence: 81%
“…[12]; however, no complete Lagrangian was given there. Recently Tseytlin considered general non-minimal N = 4 conformal supergravities, and concluded that they are free of conformal anomalies given that four vector multiplets are added to the spectrum [123]; thus agreeing with the analysis of the minimal theory [124][125][126]. A complete bosonic action for all N = 4 non-minimal conformal supergravity theories -parametrized by a free function -has been proposed by Butter, Ciceri, de Wit and Sahoo [127].…”
Section: Introductionmentioning
confidence: 69%
“…Althought such theories are power-counting renormalizable, their one-loop beta-functions are be non-vanishing [45] and therefore they suffer from a conformal anomaly. The latter leads to serious problems since conformal symmetry is gauged in Weyl gravity and therefore leads to inconsistencies [46][47][48]. The same conclusion can be drawn by considering the chiral gauge anomalies of the SU(4) R-symmetry [49] and recalling that all anomalies are accommodated in the same multiplet of the N = 4 superconformal symmetry.…”
Section: Discussionmentioning
confidence: 73%